The Emergence of Spin Magnetic Moment of Electron Inside a Photon - Boldyreva , Liudmila B. (Current Perspective to Physical Science Research Vol. 3, 2023)
The purpose of this work is to demonstrate the viability of a fundamentally novel approach to the definition of the spin magnetic moment of the electron. In contrast to previous formulations of the spin magnetic moment that accounted for the interaction of the electron with the physical vacuum, it is demonstrated in this study that the Bohr magneton, which makes up the majority of the moment, is a characteristic of photons. A "transfer" of the magnetic moment from the photon to the emerging electron-positron pair occurs when a photon decays into an electron and positron. This is comparable, for example, to the "transfer" of the spin from a photon to the emerging electron and positron pair. The so-called radiative correction to the primary component of the electron spin magnetic moment is also demonstrated in this work, and it can be calculated from the magnetic moments of virtual photons that the electron generated in the actual vacuum. The properties of virtual photons were similar to those of photons performing the propagation of the electromagnetic oscillations as well.